Amyloid β-Induced Redistribution of Transcriptional Factor EB and Lysosomal Dysfunction in Primary Microglial Cells - Guo, Xingzhi; Tang, Peng; Chen, Li; Liu, Peng; Hou, Chen; Zhang, Xin; Liu, Yue; Chong, Li; Li, Xiaoqing; Li, Rui (Frontiers in Aging Neuroscience, 2017)
Impaired clearance of Amyloid β (Aβ) by microglia in the brain may be associated with the senile plaque formation, a pathological hallmark relevant to Alzheimer’s disease. Microglial cells in the brain are not able to efficiently degrade Aβ, suggesting that microglial lysosome impairment may occur. However, the mechanism of Aβ-induced impairment of microglia remains poorly understood. We observed the effects of Aβ on the trafficking of nuclear transcriptional factor EB (TFEB), a master regulator of lysosome biogenesis，and the expression of a downstream osteoporosis-associated transmembrane protein 1 (OSTM1), a vital molecule involved in lysosome acidification in primary microglial cells. Aβ1-42 but not Aβ42-1 resulted in a significant release of tumor necrosis factor-α in primary microglia, but the total cellular TFEB was not changed. Further, Aβ induced a dose-dependent reduction of the TFEB in the nucleus of primary microglial cells, coincident with the increase in the plasma, as revealed by Western blot and confocal microscopy. In addition, a dramatic decrease of OSTM1 expression was observed in the Aβ-challenged microglial cells, along with the intracellular pH steadystate, indicating the inadequate lysosomal acidification. These data suggest that Aβ might result in a lysosomal dysfunction via inhibiting nuclear TFEB translocation in microglial cells.